In vitro comparison of Biodentine and Riva LC interfaces with cervical dentin and Filtek Z350 in posterior class II open sandwich restorations - Aguir Mabrouk Najet; Kasdallah Sawsan; Ziada Saida; Ben Salem Kamel (Wolters Kluwer Medknow Publications, 2020)
Class II open sandwich restorations are routinely performed with resin-modified glass ionomer cement as a dentin substitute and with composite resin as an enamel substitute. Biodentine™ is a new calcium silicate-based material. Various authors have evaluated the microleakage of composite resin restorations, where different resin-modified glass ionomer cements and Biodentine, used as a dentin base, were compared in class II open sandwich restorations. The aim of this study was to evaluate and to compare in vitro the sealing ability of Biodentine™ and Riva LC with cervical dentin and Filtek Z350 in posterior proximal restorations using the dye penetration test.